A RETROSPECTIVE CLINICAL AUDIT OF QUALITY OF INDIRECT DIGITAL INTRAORAL RADIOGRAPHS TAKEN BY STUDENTS AND DENTAL ASSISTANTS IN AN UNDERGRADUATE DENTAL CLINIC - Nalawade, Triveni; Shereiqi, Siham Al; Nahdi, Raqiya Al; Mallikarjuna, Rachappa; Saraf, Sanjay; Senaidi, Amer Al; Ismaily, Mohamed Al; Qutieshat, Abubaker (Quality : Jurnal Kesehatan, 2024)
Background: Intraoral radiographs are essential diagnostic tools in dentistry. Ensuring their quality is crucial for accurate diagnosis and treatment planning. This study compared the quality of radiographs produced by undergraduate dental students and qualified dental assistants to identify common errors and assess improvements following feedback and interventions. Methods: This retrospective, observational study compared the quality of digital bitewing and periapical radiographs taken by students and assistants across two audit cycles, with feedback provided between cycles. The radiographs were assessed using a modified quality assessment scale based on the Faculty of General Dental Practice (FGDP, UK) guidelines. Data were collected from the radiology imaging software, and a total of 100 intraoral digital radiographs were analyzed for each group in both cycles. Results: Initially, radiographs from both groups had issues, primarily positioning errors. After providing feedback and additional training, significant improvements were observed from Cycle 1 to Cycle 2. Dental assistants had a higher percentage of acceptable periapical radiographs, while students excelled in bitewing radiographs. Both groups demonstrated marked improvements, reflecting the effectiveness of the interventions. Conclusions: Continuous training, feedback, and quality assurance measures are vital for improving radiograph quality. A multifaceted approach, including updated equipment and adherence to quality control protocols, can significantly enhance patient care. The study highlights the importance of regular calibration and training for dental professionals to maintain high standards in radiographic practices. Further research is recommended to identify additional strategies for improving radiographic quality.